2017
DOI: 10.1016/j.bbadis.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 signaling pathway: Pivotal roles in inflammation

Abstract: Inflammation is the most common feature of many chronic diseases and complications, while playing critical roles in carcinogenesis. Several studies have demonstrated that Nrf2 contributes to the anti-inflammatory process by orchestrating the recruitment of inflammatory cells and regulating gene expression through the antioxidant response element (ARE). The Keap1 (Kelch-like ECH-associated protein)/Nrf2 (NF-E2 p45-related factor 2)/ARE signaling pathway mainly regulates anti-inflammatory gene expression and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
951
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,368 publications
(1,068 citation statements)
references
References 149 publications
23
951
0
15
Order By: Relevance
“…During IRI, the damaged tissue produces excessive amounts of ROS, causing oxidative stress that results in mitochondrial oxidative phosphorylation, ATP depletion, increases in intracellular calcium, and activates membrane phospholipid proteases [37]. Nrf2 and Keap1 are two major proteins in the immune reaction that act as a complex in the cytoplasm to control intracellular oxidative stress [13, 38]. Tan et al found that upregulating Keap1 in hypomorphs protected mice against IRI, and was associated with a reduction in inflammatory gene expression and upregulation of Nrf2 target genes [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During IRI, the damaged tissue produces excessive amounts of ROS, causing oxidative stress that results in mitochondrial oxidative phosphorylation, ATP depletion, increases in intracellular calcium, and activates membrane phospholipid proteases [37]. Nrf2 and Keap1 are two major proteins in the immune reaction that act as a complex in the cytoplasm to control intracellular oxidative stress [13, 38]. Tan et al found that upregulating Keap1 in hypomorphs protected mice against IRI, and was associated with a reduction in inflammatory gene expression and upregulation of Nrf2 target genes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Kelch-like ECH-associated protein 1 (Keap1) binds Nrf2 in the cytoplasm, forming a complex that maintains Nrf2 at a low and steady level [12]. When IRI occurs, Keap1 undergoes conformational change and activates Nrf2, resulting in cellular protection against oxidative stress and enhancement of cell growth and survival [12, 13]. Hemeoxygenase-1 (HO-1) is one of the antioxidant response element (ARE)–dependent phase II detoxifying enzymes and antioxidants that are regulated by the redox-sensitive transcription factor Nrf2 [14-16].…”
Section: Introductionmentioning
confidence: 99%
“…have been developed by cells to remove ROS and many of them are transcriptionally regulated by Nrf-2 (Nuclear factor erythroid 2-related factor 2), the master regulator of antioxidant response. Nrf2 is a transcription factor that in normal conditions is inhibited by Keap-1 (Kelch-like ECH-associated protein 1) that targets Nrf2 for ubiquitination and proteasomal degradation [12]. Under stress conditions, Nrf2 is stabilized and allows survival and stress adaptation upregulating the expression of some cytoprotective molecules, the antioxidant responses and the stress-mediated detoxification enzymes (NAD(P)H quinina reductase, glutathione S-transferase, superoxide dismutase, heme oxygenase, catalase and glutathione peroxidase) [13].…”
Section: Antioxidant Properties Of Mangifera Indica Lmentioning
confidence: 99%
“…Na verdade, as vias de sinalização do Nrf2 e do NFκB interagem de forma complementar e especializada para a manutenção da homeostase celular. Contudo, devido à continuidade dos estímulos da inflamação crônica, a ativação do NFκB se sobressai, ocasionando morte celular, destruição tecidual e fibrose 23 . Tal processo pode ser observado em ilhotas pancreáticas de camundongos com inflamação crônica sistêmica desencadeada pela administração de lipopolissacarídeo, situação na qual ocorre ativação de vias inflamatórias dependentes de NFκB, aumento do dano oxidativo e de vias pró-apoptóticas e redução da translocação nuclear de Nrf2 24 .…”
Section: Relação Entre Nrf2 E Inflamaçãounclassified